Social support and physical activity in adolescents: evidence from a correlational approach - Fahrezy, Rendy; Ma’mun, Amung; Carsiwan; Syarifatunnisa; Anira (Edu Sportivo: Indonesian Journal of Physical Education, 2025)
Background: Amid rising sedentary behaviors and non-communicable diseases among adolescents globally, physical activity levels continue to decline—exacerbated by lifestyle shifts driven by globalization. While social support is often considered a key enabler of behavior change, limited empirical evidence clarifies its actual influence on adolescent physical activity, particularly in diverse sociocultural settings like Indonesia. This study addresses that gap. Research Objectives: This study aimed to examine the relationship between perceived social support and physical activity among adolescents in two different school settings. Methods: A correlational quantitative design with convenience sampling was employed, involving 1.046 adolescents aged 12–18 years from two schools with differing neighborhood contexts. Social support was assessed using the Multidimensional Scale of Perceived Social Support (MSPSS), and physical activity levels were measured using the Global Physical Activity Questionnaire (GPAQ). Data were analyzed using Spearman rank correlation via SPSS. Finding/Results: The results of data analysis using the Spearman rank test showed no significant relationship between physical activity and all components of social support (family, friends, and others) p> 0.05 (p=0.222, r=-0.038 for family; p=0.143, r=0.045 for friends; p=0.717, r=0.011 for significant others; p=0.779, r=0.009 for overall social support). Conclusion: These results indicate that social support is not the main factor influencing physical activity participation in adolescents. This study showed no significant relationship between the two variables. Other factors such as physical literacy, intrinsic motivation, school environment, and health conditions may have a more dominant role. Future studies are expected to explore these factors through longitudinal and experimental approaches.